Fanlec: blog educativo “fanáticos de la lectoescritura” para el mejoramiento de la competencia de lectoescritura en los estudiantes de básica primaria (2023)
This research project arises from the need to make the literacy process fun in primary school children, who in some cases have a deficiency in these skills, which makes it difficult for them to read and write correctly. That is why the general objective is focused on implementing an educational blog for the improvement of literacy in primary students of the José María Córdoba Educational Institution. Regarding the methodology used, it is a quantitative approach with a pre-experimental design. The participants are made up of a sample of 31 students from grade 5°1. For data collection, techniques and instruments such as the survey and a test (Postest) were used to compare the results obtained with the results of the initially applied test (Pretest). Once analyzed, it was found that the educational blog "Fanatics of Literacy" contributed to a greater learning in terms of reading and writing of the students.